Comparative study of minimal fresh gas flow used in Lack-Plus and Lack’s circuit in spontaneously breathing anesthetized adults - Theerapongpakdee S (Medical Devices : Evidence and Research, 2016)
Sunchai Theerapongpakdee, Thepakorn Sathitkarnmanee, Sirirat Tribuddharat, Siwalai Sucher, Maneerat Thananun, Duangthida Nonlhaopol Department of Anesthesiology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand Background: The Lack’s circuit is a co-axial Mapleson A breathing system commonly used in spontaneously breathing anesthetized adults but still requires high fresh gas flow (FGF). The Lack-Plus circuit was invented with the advantage of lower FGF requirement. The authors compared the Lack-Plus and Lack’s circuit for the minimal FGF requirement with no rebreathing in spontaneously breathing anesthetized adults.Methods: This was a randomized crossover study. We enrolled 24 adult patients undergoing supine elective surgery, with a body mass index ≤30 kg/m2 and an American Society of Anesthesiologists physical status I–II. They were randomly allocated to group 1 (LP-L) starting with Lack-Plus then switching to Lack’s circuit or group 2 (L-LP) (with the reverse pattern). After induction and intubation, anesthesia was maintained with 50% N2O/O2 and desflurane (4%–6%) plus fentanyl titration to maintain an optimal respiratory rate between 10 and 16/min. Starting with the first circuit, all the patients were spontaneously breathing with a FGF of 4 L/min for 10 min, gradually decreased by 0.5 L/min every 5 min until FGF was 2.5 L/min. End-tidal CO2, inspired minimum CO2 (ImCO2), mean arterial pressure, and oxygen saturation were recorded until rebreathing (ImCO2 >0 mmHg) occurred. The alternate anesthesia breathing circuit was used and the measurements were repeated.Results: The respective minimal FGF at the point of rebreathing for the Lack-Plus and Lack’s circuit was 2.7±0.8 and 3.3±0.5 L/min, respectively, p<0.001. At an FGF of 2.5 L/min, the respective ImCO2 was 1.5±2.0 and 4.2±2.6 mmHg, respectively, p<0.001.Conclusion: The Lack-Plus circuit can be used safely and effectively, and it requires less FGF than Lack’s circuit in spontaneously breathing anesthetized adults. Keywords: spontaneous breathing, anesthesia, non-rebreathing anesthetic circuit, modified Mapleson A breathing system, coaxial breathing system, rebreathing